SEJARAH PERKERETAAPIAN MEDAN (1886-1942) - Haston Ranap Erwin; Ridwan Melay; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Rail is a form of rail transport consisting of a series of vehicles drawn along a railway line to transport cargo or passengers. The railways are inseparable from a Dutch arrival to Indonesia. In 1886, the Dutch government built the Medan Station. This station is used to transport the plantation to the port. This research aims to (1) to know the history of Medan railway, (2) to know the development of railway in Medan 1886-1942, (3) to know the influence of railway existence in Medan there are indigenous society in the field of social-economy. The method used in this research is qualitative method. Qualitative method is a method that does not use numbers in data collection and in giving interpretation of the results. Data obtained from interviews are then analyzed in their own language. The location of the research is in Medan, precisely in Jalan Prof. H.M. Yamin. Research starts from proposal seminar to thesis exam. Data collection techniques used were interview techniques, documentation techniques, library study techniques and comporative studies. Keywords: Railways, Medan.